Lysosomal Ca2+ Signaling Regulates High Glucose-Mediated Interleukin-1β Secretion via Transcription Factor EB in Human Monocytic Cells - Tseng, Hisa Hui Ling; Vong, Chi Teng; Kwan, Yiu Wa; Lee, Simon Ming-Yuen; Hoi, Maggie Pui Man (Frontiers in Immunology, 2017)
Aberrant activation of the innate immune system, including NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome-dependent interleukin-1β (IL-1β) secretion, has been implicated in the pathogenesis of Type 2 Diabetes Mellitus (T2DM) and its complication. Our previous study demonstrated that hyperglycemia, a hallmark characteristic of T2DM, induced NLRP3 inflammasome-dependent caspase-1 activation and IL-1β maturation in human monocytoc cells. In this study, we examined the underlying mechanisms of secreting IL-1β during hyperglycemia, with a focus on the alteration of Ca2+ homeostasis and lysosomal exocytosis. We found that high glucose (HG; 30mM glucose for 48h) altered Ca2+ homeostasis by reducing lysosomal Ca2+ concentration that appeared to be resulted from Ca2+ moving out of lysosomes into cytosol in human monocytic cell lines, U937 and THP-1 cells. Moreover, HG-induced lysosomal Ca2+-dependent mature IL-1β release was strongly correlated with the activation and up-regulation of two lysosomal marker proteins, cathepsin D and Lysosomal-associated membrane protein-1 (LAMP-1). This involved calcineurin/Transcription factor EB (TFEB) pathway and its target genes, cathepsin B, cathepsin D and LAMP-1, to mediate lysosomal exocytosis. Therefore in this study, we revealed a novel mechanism of HG-induced lysosomal exocytosis which was regulated by lysosomal Ca2+ signals through calcineurin/TFEB pathway, thus contributing to IL-1β secretion in human monocytic cells.